Leadership Education System in Education Management in Industry 4.0 Era - Monoarfa, Haris; Rawis, Joulanda A.M; Tambingon, Henny N.; Kambey, Joseph (International Journal of Information Technology and Education, 2023)
Education in the industrial era 4.0 is a considerable challenge, because in order to realize good management in education to form leadership, adjustments to the curriculum, learning systems, supporting facilities and infrastructure and good human resources are needed. Not only that, in the industrial era, we must be able to build partnerships with various stakeholders to realize good management. Industry 4.0 can create artificial intelligence where the characteristics or behavior of a human being can be included in the application, so that humans are required to adapt to the current conditions of development.